Análise de desempenho de um sistema COFDM para comunicação via rede elétrica - Silva, Jair Adriano Lima (2006)
The Internet popularization demands for inexpensive installation and provision of the access technologies and services. Power Line Communication (PLC) technology is a promising alternative since it uses the existing infrastructure of the distribution power network as a high-speed data channel. In order to implement advanced communication systems over hostile PLC channels, complete knowledge of its transfer function and its intrinsic noises are required. This thesis analyzes multicarrier Orthogonal Frequency Division Multiplexing (OFDM) communication systems for Internet access and home networking over both outdoor and indoor power line channel models. A trellis coded modulation OFDM (COFDM) system is proposed an its performance is compared with the classic OFDM system in terms of Bit Error Rate (BER) versus Signal-to-Noise Rate (SNR). A particular indoor power distribution system was built in order to obtain the transfer function and noise used in the simulations. Simulation results had shown coding gains up to 8 dB at 10−6 BER in COFDM with one tap equalizer.